Enhancing E-Loyalty in Tokocrypto: The Impact of E-Service Quality and E-Trust Mediated by E-Satisfaction - Siska Amelia Putri; Osly Usman; Nofriska Krissanya (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to gain new knowledge and analyze the influence of e-service quality and e-trust on e-loyalty, through e-satisfaction among users of the tokocrypto application. This type of research is quantitative research using a survey method through questionnaires distributed boldly, with the population used being tokocrypto users who live in DKI Jakarta. The sampling technique used was purposive sampling technique with a total sample of 210 respondents. The analysis technique used to process the collected data is validity and reliability testing with Smart PLS, and hypothesis testing using Structural Equation Modeling (SEM) with PLS Sofware.